Acute splenic rupture following laparoscopic pneumoperitoneum: A case report. (August 2019) - Delafontaine, Jean-Luc; Moreci, Rebecca; Samra, Navdeep S.
Abstract: Introduction: Splenic rupture after laparoscopic surgery is a very rare complication. In this study, we report a case of a splenic laceration that occurred during a laparoscopic gastrostomy tube placement. The theorized mechanism in this case was acute disruption of a peri-splenic hematoma. Case report: A 64-year-old African-American male presented after a motor vehicle accident with multiple injuries and was admitted to a surgical intensive care unit, where he declined from ICU days 6 through 11. The patient underwent tracheostomy and laparoscopic gastrostomy tube placement given his significant neurologic deficits. Intraoperatively, the patient developed hypotension, leading to the discovery of hemoperitoneum and necessitating an emergent open splenectomy. Conclusion: Splenic rupture following laparoscopic procedures is a very rare phenomenon. In this case, we believe the splenic rupture was secondary to an acute disruption of a previously hemostatic splenic hematoma involving the abdominal wall during creation of capnoperitoneum.